THE EXPRESSION OF THE POTENTIAL OF LITHUANIAN MUNICIPALITIES IN THE FIELD OF SMART PUBLIC GOVERNANCE AND SMART SOCIETY - Martinaitis, Tomas (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The article analyses the fields of smart public governance and smart community in the Lithuanian municipal system. Based on the authors’ works, that investigated the concept of a smart social system and such smart systems as smart public governance and smart community, the appropriate models of these systems were developed for Lithuanian local self-governance. It was found that in the case of municipalities, in the field of smart public governance, strategic dynamism, inter-sectoral cooperation/networking, and empowered citizenship are treated similarly, and the dimension of inter-institutional cooperation is slightly weaker compared to the other mentioned dimensions. In the case of the smart community, digitalisation, knowledgedriven, learning, and sustainability dimensions stand out, while the dimensions of networking, innovation, and agile response are rated slightly lower, while intelligence and social responsibility are rated the lowest of all the dimensions assessed. Such insights have been based on expert interviews. Key words: smart social system, smart municipality, smart public governance, smart community.